PENINGKATAN KETERAMPILAN MENULIS KARANGAN NARASI DENGAN MENGGUNAKAN TEKNIK MENERUSKAN CERITA SISWA KELAS X IPA 1 SMA N 1 MUTIARA - Rahmiyanti Rahmiyanti (Fakultas Keguruan dan Ilmu Pendidikan Universitas Jabal Ghafur, 2022)
This type of research is classroom action research (CAR). Classroom action research can be defined as a form of reflective study, meaning that research is carried out to improve the rational ability of the actions taken, as well as improve the conditions in which the learning practice is carried out. Classroom action research is carried out in four stages, namely: (1) planning, (2) action, (3) observation or observation, and (4) reflection. This study uses two variables, namely the skill of writing narrative essays and the technique of continuing the story. Data collection was divided into two stages, namely cycle I and cycle II using test and non-test techniques with the application of learning techniques. The test used is an action test in the form of an assignment to write a narrative essay, while the non-test technique used is in the form of observation, journaling, interviews, and photo documentation. This research uses qualitative and quantitative data analysis techniques. Quantitative techniques were used to analyze and compare the test results of the cycle I and cycle II. Meanwhile, qualitative techniques were used to analyze and compare the results of the non-test in cycle I and cycle II. The results of this study indicate an increase in narrative essay writing skills with the technique of continuing the story in class X IPA 1 SMA N 1 Mutiara. The average value at the stage of the first cycle is 67.8. in the second cycle to 79.43. The results of non-test data analysis showed an increase in the behavior of class X IPA 1 students of SMA N 1 Mutiara in a positive direction. Students become more enthusiastic about participating in learning to write news texts. Based on the results of this study, the authors suggest that Indonesian language teachers use story-telling techniques in learning to write narrative essays. It is recommended for students to be more active and creative in learning activities in order to overcome learning difficulties and have fun while participating in learning activities. Finally, it is intended that researchers are expected to conduct research using other learning techniques to increase the repertoire of language knowledge.Keywords : writing skills, narrative essay, and story-telling techniques